uTango: an open-source TEE for IoT devices - Oliveira, Daniel José Cunha (2022)
Security is one of the main challenges of the Internet of Things (IoT). IoT devices are mainly powered by low-cost microcontrollers (MCUs) that typically lack basic hardware security mechanisms to separate security-critical applications from less critical components. Recently, Arm has started to release Cortex-M MCUs enhanced with TrustZone technology (i.e., TrustZone-M), a system-wide security solution aiming at providing robust protection for IoT devices. Trusted Execution Environments (TEEs) relying on TrustZone hardware have been perceived as safe havens for securing mobile devices. However, for the past few years, considerable effort has gone into unveiling hundreds of vulnerabilities and proposing a collection of relevant defense techniques to address several issues. While new TEE solutions built on TrustZone-M start flourishing, the lessons gathered from the research community appear to be falling short, as these new systems are trapping into the same pitfalls of the past. In this paper, we present UTANGO, the first multi-world TEE for modern IoT devices. UTANGO proposes a novel architecture aiming at tackling the major architectural deficiencies currently affecting TrustZone(-M)-assisted TEEs. In particular, we leverage the very same TrustZone hardware primitives used by dual-world implementations to create multiple and equally secure execution environments within the normal world. We demonstrate the benefits of UTANGO by conducting an extensive evaluation on a real TrustZone-M hardware platform, i.e., Arm Musca-B1. UTANGO will be open-sourced and freely available on GitHub in hopes of engaging academia and industry on securing the foreseeable trillion IoT devices.